Digital Health Governance in Iran: A Situational Analysis and Future Scenarios - Neshat Kafash, Asal; Pourezzat, Ali Asghar; Rezayan, Ahad (Journal of Foresight and Health Governance, 2026)
Background: Despite extensive technological investments, the transition to digital health governance in developing systems is often trapped in institutional inertia. Existing literature largely suffers from a retrospective bias, overlooking how emerging legal mandates reshape future trajectories. This study critically examines the contested field of digital health governance in Iran, specifically focusing on the structural tensions introduces by the 7th National Development Plan (2024–2029).Methods: Adopting a Hybrid Prospective Qualitative Design, this research integrates Adele Clarke’s Situational Analysis with a Scenario Planning framework. Empirical data were drawn from 18 in-depth interviews with elite stakeholders and a critical analysis of key policy documents. Based on the identified governance logics and data regimes, a matrix was constructed to map plausible futures for the 2035 horizon.Results: The analysis reveals a governance deadlock where the state’s drive for data centralization—codified through the Regulator-Operator model—clashes with the needs of an innovation ecosystem. Four divergent future paths are identified: 1.Digital Stagnation (a path-dependent outcome of current bureaucratic silos), 2.The Digital Panopticon (efficient technical integration under strict authoritarian surveillance), 3.Innovation Islands (fragmented private success without national scaling), and 4.The Dynamic Ecosystem (participatory governance treating data as a public good). Findings suggest that current legal mandates are actively steering the system toward the first two scenarios.Conclusion: The transition to a sustainable digital health ecosystem is not merely a technical challenge but a political one. Avoiding the trap of a Digital Panopticon requires a fundamental institutional reconfiguration: shifting from the sovereign asset framing of health data toward a participatory governance model that balances state stewardship with ecosystem agency.